For function A below, I get a different result when I use "est += XXX" as compared to using "est = est + XXX". The former gives a result of 1.33227e-15 while the latter gives an result of 8.88178e-16.

On the other hand, for function B below, I get the same result regardless of whether I use "est += XXX" or "est = est + XXX"

Would anyone be able to explain why x+=y is equivalent to x=x+y in function B but not A?

**function A**

```
double A(int nTerm){
const double PI = 3.141592653589793238463;
double est = 0;
double counter = 0;
do {
est += ( 16 * pow(-1,counter) )/ (2*counter+1) * pow((double)1/5, 2*counter+1)
- ( 4 * pow(-1,counter) )/ (2*counter+1) * pow((double)1/239, 2*counter+1);
counter++;
} while (counter<=nTerm);
return est-PI;
}
```

**function B**

```
double B(int nTerm){
double est = 0;
double counter = 0;
do {
est += counter;
counter++;
} while (counter<=nTerm);
return est;
}
```

### >Solution :

`x += y - z`

is the equivalent to `x = x + ( y - z )`

. You likely wrote `x = x + y - z`

. You need to enforce precedence. See here that with the brackets, the return values are the same.

In your case, you want:

```
est = est + ( ( 16 * pow(-1,counter) )/ (2*counter+1) * pow((double)1/5, 2*counter+1)
- ( 4 * pow(-1,counter) )/ (2*counter+1) * pow((double)1/239, 2*counter+1) );
```

Note: when dealing with double values, `A + B - C`

can be very different than `A + ( B - C )`

even though they *should* be the same. See Is floating point math broken?